Design and scale-up of continuous di-nitration reaction using pinched tube flow reactor - Hussain, Arshad; Sharma, Mrityunjay; Patil, Suneha; Acharya, Roopashree B.; Kute, Mahesh; Waghchaure, Aishwarya; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Scale-up of the di-nitration reaction for synthesis of selective herbicide pendimethalin using only nitric acid in continuous flow is presented in this work. This work showcases an approach for smooth scale-up for an herbicide for a production capacity of 50 kg/day using a pinched tube reactor. The approach begins with the batch experiments followed by flow synthesis using a 1/8-inchSS316 helical coil tube where kinetics of the di-nitration was determined, and process optimization was done. Systematic approach was followed for quantification of heat transfer, mass transfer and residence time distribution and scale-up. Detailed scale-up methodology is presented with effect of relevant parameters for successful scale-up. Modular pilot plant with inline quenching, extraction and separation are some of the salient features presented in this work.
Keywords: continuous flow; nitration; Pinched tube; RTD; scale-up